New Optical Tools to Study Neural Circuit Assembly in the Retina - Rangel Olguin, Aline Giselle; Rochon, Pierre-Luc; Krishnaswamy, Arjun (Frontiers in Neural Circuits, 2020)
During development, neurons navigate a tangled thicket of thousands of axons and dendrites to synapse with just a few specific targets. This phenomenon, termed wiring specificity, is critical to the assembly of neural circuits; the way neurons manage this feat is only now becoming clear. Recent studies in the mouse retina are shedding new insight into this process. They show that specific wiring arises through a series of stages that include: the directed axonal and dendritic growth, the formation of neuropil layers, the positioning of such layers, and the matching of co-laminar synaptic partners. Each stage appears to be directed by a distinct family of recognition molecules, suggesting that combinatorial expression of such family members might act as a blueprint for retinal connectivity. By reviewing the evidence in support of each stage, and by considering their underlying molecular mechanisms, we attempt to synthesize these results into a wiring model which generates several testable predictions for future studies. Finally, we conclude by highlighting new optical methods that could be used to test such predictions and gain further insight into this fundamental process.